Cu2O quantum dots redefining photodynamic therapy with one-minute pathogen inactivation under visible light - Azzah Dyah Pramata; Farhan Aryo Hutomo; Febriyansyah Saputra; Paundra Rizky Pratama; Taras Geonovive De Yenarosa; Sutarsis; Sigit Tri Wicaksono; Agung Purniawan; Revianny Nidom; Shao-Yang Hu (Case Studies in Chemical and Environmental Engineering)
This work utilizes tailored – Cu2O quantum dots (QDs) to demonstrate unprecedented pathogen photo-inactivation. The superior ROS production of the QDs synthesized at 180 °C with a size of 8.10 nm resulted in a 99.98 % reduction of MRSA, 99.78 % of Klebsiella pneumoniae, and 98.92 % of SARS-CoV Delta within 1 min under visible light. Cu2O QDs efficiently reduced 99.25 % viability of 4T1 cancer cells in 15 min while maintaining more than 85 % viability in healthy HEK 293 cells, underlining its selectivity. This finding may establish Cu2O QDs as the next-generation anti-pathogen agents for advanced photodynamic therapy (PDT), biomedical sterilization, and hospital applications.